If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6y + 32 = 68 Reorder the terms: 32 + 6y = 68 Solving 32 + 6y = 68 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-32' to each side of the equation. 32 + -32 + 6y = 68 + -32 Combine like terms: 32 + -32 = 0 0 + 6y = 68 + -32 6y = 68 + -32 Combine like terms: 68 + -32 = 36 6y = 36 Divide each side by '6'. y = 6 Simplifying y = 6
| F(X)=X^5-5X^4 | | 5-3x=11 | | 5(x+4)=3(3x-1)-9 | | x+4(x-4)=0 | | 54x+9y=72 | | 1+.80x=2.75x | | 12n^2+3=0 | | 1+1=121 | | 21/2y=11/4y-8 | | X-1.4=1.9 | | 2(8+6y)=4(2y-12) | | 6(n+7)-6n= | | 78x=12x-80 | | (2x^2)+4x-1=0 | | -2(4x-5)=-90 | | 3v-2(-v+7)=2(1+3v) | | -4(-5-3x)=18 | | 5y+2y-3=9y-8 | | 5x-8y+18=0 | | 5w-6-8w=12 | | 3(x+4)-9=0 | | 6n^2-13n+6= | | 8y+6x=2x-10y | | 5y+4y+3=66 | | 2x^2+w-21=0 | | 15x=40+25 | | 2x+5+4x=35 | | 10x=80-10 | | X^4-50x=-49 | | 7x+3-4x=7 | | t-115=10 | | 2a+3b=-18 |